ON THE TRANSITION BETWEEN FERROMAGNETIC AND PARAMAGNETIC STATES IN MESOPOROUS MATERIALS WITH FRACTAL MORPHOLOGY - Shishulin, A.V.; Potapov, A.A.; Shishulina, A.V. (KU Publ., 2021)
In this paper, we have shown how the presence of pores and pore morphology influence on magnetic phase transition temperatures in mesoporous ferromagnetic materials. Model calculations have demonstrated the possibility to obtain macroscopic mesoporous samples with notably reduced Curie temperatures which is also further depressed in the case the pore morphology is more complicated. The results have been obtained on the basis of the experimentally verified correlation between the Curie temperature and cohesive energy of the material and illustrated using the examples of pure mesoporous iron, nickel and cobalt while pore morphology has been determined by the methods of fractal geometry. Several practical applications of mesoporous materials with tuned values of the Curie temperature have also been discussed in the final section.
Keywords: mesoporous materials; second-order phase transition; ferromagnetism; Curie temperature; cohesive energy